Baseball sports medicine - Ahmad, Christopher S.; Romeo, Anthony A. (Wolters Kluwer, 2019)
"Baseball, America's pastime, is an incredible sport that defies the capabilities of the human body and fascinates everyone it touches. Unfortunately, we are in the midst of a crisis of ever increasing injuries to those playing this beloved sport. Baseball Sports Medicine textbook is the product of an educational platform that facilitates the interaction of the world's experts in baseball medicine. The Baseball Sports Medicine: Game-Changing Concepts conference has been held at the Major League Baseball (MLB) offices on Park Avenue in New York City and has been sold out every year since its introduction. The textbook chapters are constructed in typical fashion with history, physical examination, imaging, and treatment, but also includes 46 inspirational baseball quotes, side bar explanations called "Trip to the Mound," and chapter summaries called "Manager's Tips." The latest advancements in baseball technology and care are included with remarkable illustrations and clear explanations"--Provided by publisher